Designing Query Optimization for Scheduling the Lecture Across Faculties and Study Programs - Joko Aryanto; Ahmad Tri Hidayat (University of Technology Yogyakarta, 2021)
One of the implementation models of combinatorial optimization that has a high complexity is the preparation of lecture schedules. Scheduling optimization needs to be optimized based on the schedule reference constraints. This study aims to design an optimization model with dynamic scheduling slots every day. The method used is query re-optimization with schedule distribution in accordance with predetermined limits. The models designed include space models, lecture times, and schedules. The model uses data that is in sync with the schedule, such as classrooms (theory and practice), credit and course loads (odd and even), lecturer schedules (teaching) and course time slots, as well as lecture sessions per day. This research is able to produce an optimal class schedule with all combinations of plotted schedules. The results of plotting the schedule are as desired and there are no conflicting schedules.